Studi Komparatif Rasa Syukur Dalam Tafsir Fi Dzilalil Qur’an dan Tafsir Mafatihul Ghaib : Surat Al-Baqarah 152 dan Ibrahim Ayat 7 - Achmad Sofiyul Mubarok; Ahmad Surur (Fikr: Jurnal Pemikiran Studi Islam, 2026)
This research examines and tries to reconstruct the understanding and application of human gratitude. Gratitude is often forgotten in any situation and circumstance, especially when there is an abundance of blessings. Whereas if the sense of Gratitude continues to be realized and attached to the mind and soul, it will produce humanist silat both theological and social sides. Then this research serves as a complement to previous studies by discussing aspects of Gratitude that have been neglected. By adopting qualitative research, this study collects data from a predetermined tafsir, as well as in journals, articles, books and other relevant literature. And with the comparative method (Muqaran), this research reveals that there are differences in interpretation in Tafsir Fii Dzilalil Qur'an and Tafsir Mafatihul Ghaib towards Surah Baqarah 152 and Ibrahim Verse 7. This research proves that the differences in interpretation are caused by the background of the author of the interpretation and the social dynamics that overshadow it. Therefore, the explanation of gratitude can be drawn, namely gratitude is a dialogic process with Allah. So that if done daily, it is believed that it will feel closer to Allah SWT. And gratitude is also considered to have a humanist nature, because interactions and relationships with humans will be worth high tolerance.